The impact of a multidisciplinary team intervention on medication prescription in nursing homes in Catalonia - Anderssen-Nordahl, Emilie; Fernández-Liz, Eladio; Sabaté Gallego, Mònica; Bosch Ferrer, Montserrat; Sánchez-Arcilla Rosanas, Margarita; Cervera León, Mercè; Magrinyà, Joaquim Miquel; Barceló-Colomer, Maria Estrella (Frontiers in Pharmacology, 2024)
In response to the rising population of nursing home residents with frailty and multimorbidity, optimizing medication safety through drug utilization review and addressing medication-related problems (MRPs) is imperative. Clinical decision support systems help reduce medication errors and detect potential MRPs, as well as medication reviews performed by a multidisciplinary team, but these combined assessments are not commonly performed. The objective of this study was to evaluate the impact on medication plans of a multidisciplinary team intervention in nursing homes, by analyzing the medication plan before and after the intervention and assessing whether the recommendations given had been implemented.A multicenter before-after study, involving five nursing homes, assessed the impact of a multidisciplinary team intervention, to estimate effectiveness related to the review of the prescribed medications. The follow-up period for each patient was 12 months or until death if prior, from July 2020 to February 2022, and involved 483 patients. The clinical pharmacologist coordinated the intervention and reviewed all the prescribed medications to make recommendations, focused on the completion of absent data, withdrawal of a drug, verification of whether a drug was adequate, the substitution of a drug, and the addition of drugs. Since the intervention was performed during the COVID-19 pandemic, optimization of psychotropic drugs and absorbent pads were limited.The intervention had an impact with recommendations given for 398 (82.4%) of the patients and which were followed by 58.5% of them. At least one drug was withdrawn in 293 (60.7%) of the patients, with a mean of 2.3 (SD 1.7). As for the total of 1097 recommendations given, 355 (32.4%) were followed. From the intervention, antipsychotics, antidepressants, benzodiazepines, statins, and diuretics were the most frequently withdrawn.The findings underscore the impact of targeted interventions to reduce inappropriate medications and enhance medication safety in nursing homes. The proposed recommendations given and followed show the importance of a multidisciplinary team, coordinated by a clinical pharmacologist, for a patient-centered approach to make medication reviews regularly, with the help of clinical decision support systems, to help reduce potential MRPs and polypharmacy.